Impacts of deforestation on the Southern Amazon rainy season - Leite Filho, Argemiro Teixeira (2019)
Amazonian deforestation is causing notable changes in the hydrological cycle by altering important precipitation characteristics. Past studies presented evidence that deforestation may affect the precipitation seasonality in southern Amazonia. This work provides an integrated research on how decades of deforestation in southern Amazonia have affected the regional rainy season. In Chapter 1, I used daily rainfall time series data from 112 rain gauges and a recent yearly 1-km land use dataset covering the period from 1974 to 2012 to evaluate the effects of the extent of deforestation at different spatial scales on the onset of the rainy season and on the duration of dry spells in southern Amazonia. In Chapter 2, I used daily rainfall data from TRMM 3B42 product and a recent yearly 1-km land use dataset to evaluate the quantitative effects of deforestation on the onset, demise and length of the rainy season in southern Amazonia for a period of 15 years (1998-2012). Additionally, I used Niño4 anomalies, zonal wind data and deforestation data to explain and predict the interannual variability of the rainy season onset. Using rain gauge data, correlation analyses indicate a delay in the onset of 1.2–1.7 days per each 10% increase in deforestation. Analysis of cumulative probability density functions emphasized that the likelihood of rainy season onset occurring earlier than normal decreases as the local deforestation fraction increases. In addition, the probability of occurrence of dry spells in the early and late rainy season is higher in areas with greater deforestation. Using precipitation remote sensing products, onset has delayed ∼0.38±0.05 days per year (5.7±0.75 days in 15 years), demise has advanced 1.34±0.76 days per year (20±11.4 days in 15 years) and the rainy season has shortened by 1.81±0.97 days per year (27±14.5 days in 15 years). Onset, demise and length also present meridional and zonal gradients linked to large-scale climate mechanisms. After removing the effects related to geographical position and year, I also verified a relationship between onset, demise and length and deforestation: Onset delays ~0.4±0.12 day, demise advances ~1.0±0.22 day and length decreases ~0.9±0.34 day per each 10% increase in deforestation. I also presented empirical evidence of the interaction between large-scale and local-scale processes, with interannual variation of the onset in the region explained by Niño4 sea surface temperature anomalies, Southern Hemisphere subtropical jet position, deforestation and their interactions (r2 = 69%, p < 0.001, MAE = 2.7 days). The delayed onset, advanced demise, shorter length of the rainy season and longer dry spell events in highly deforested areas increase the climate risk to agriculture in the region.